The concept of vertical take-off and landing by using UAV mini model / Abdullah Syahril Mat Jani - Mat Jani, Abdullah Syahril (2004)
This project of “The Concept Of Vertical Take-OFF And Landing (VTOL) by using Unmanned Aerial Vehicle (UAV) Mini Model” have been carried out by the final year students of UiTM Mechanical Engineering under the supervision of Pn. Junaidah Abd Rahmad, but in the middle of the semester this project was been taken over by Pn. Wan Mazlina from Pn. Junaidah due to medical reason. The important part of this project is to study some basic theory that involve in vertical take off and landing (VTOL) airplane. As we know, the VTOL airplane can be divided into two type of airplane. One is fix wing type that uses compressible engine to fly vertical and the other type is using blade to generate power to fly vertical (also known as rotary wing). From the discussion with our previous advisor Mrs. Junaidah, after considering the budget for the project, we had decided the rotary wing type of airplane to fulfill our final project. From the theoretical study of the basic concept, we will try to build a simple model of UAV base on the rotary wing type of airplane. After the model has been completed, testing were conducted to ensure the model can fly. Lastly, some recommendation are been made to improve the outstanding model. We hope from this project we could understand the basic knowledge about the VTOL rotary wing type of airplane and we are happy if this project report can be used as a guide by other students to build a better model in the future semester. We want to emphasise here that this project only cover the basic theoretical study of the VTOL airplane concept because of the budget limitation.